Emergence and Dissemination of a Community-Associated Methicillin-Resistant Panton-Valentine Leucocidin-Positive Staphylococcus aureus Clone Sharing the Sequence Type 5 Lineage with the Most Prevalent Nosocomial Clone in the Same Region of Argentina - Sola, Claudia (American Society for Microbiology (ASM), 2008)
Epidemiological surveillance for community-associated methicillin-resistant Staphylococcus aureus revealed prevalences of 33% and 13% in pediatric and adult patients, respectively, in Cordoba, Argentina, in 2005. This study describes for the first time the emergence and dissemination of the sequence type 5 (ST5) lineage as the most prevalent clone (89%) (pulsed-field gel electrophoresis type I-ST5-staphylococcal cassette chromosome type IVa-spa type 311) harboring the Panton-Valentine leukocidin and enterotoxin A genes.